Practices, recipes and supply of a late medieval brass foundry: The refractory ceramics and the metals of an early 15th century AD metallurgical workshop in Brussels. (April 2022) - Saussus, Lise; Goemaere, Eric; Thomas, Nicolas; Leduc, Thierry; Goovaerts, Thomas; Fourny, Michel
Highlights: First evidence of medieval brass production in Brussels. One of the rare 15th century mass-production metallurgical workshops known in Europe. Refractory clays for crucibles are imported from the Mosan valley to Brussels. Recipes are documented by petrographic and EDS analyses. Abstract: This article focuses on one of the rare workshops for the production of small copper-based alloy objects in the late Middle Ages documented by archaeology. Located in Brussels and dating from the early 15th century, the workshop produced a serial and varied production of dress accessories and other personal objects, mainly in brass, by casting or plastic deformation. These metal objects, mostly fashion accessories, had an important place in the medieval material culture. They are mass-produced and widely spread throughout Europe: the market is therefore very large and the techniques are adapted to satisfy this demand. This paper focuses on a workshop that adapted to this expansion while similar production structures are still largely unknown in the archaeology of northwestern Europe. It is the only one currently in the Low Countries that offers the possibility of knowing the practices and supplies. By identifying workshop practices, this contribution addresses, in particular, the properties and the supplies of the clay used, but also the different ranges of alloys and the evidence of the brass production by the cementation process, by combining several analysis methods (petrography using PLM and SEM, Energy Dispersive X-Ray Spectroscopy, PIXE, X-ray diffraction). This approach highlights different supplies, local and extra-local, as the distance was not an obstacle for the supply of high-quality crucible clay and zinc ore for brass production. These results associated with the written sources place the Brussels workshop in a wider network of circulation of raw materials and know-how related to their use. This also shows the interaction between techniques, materials and more broadly with the economy of the late Middle Ages that goes beyond the local sphere.